Analysis Of Social Media Marketing Activities and Brand Image On Brand Loyalty With Brand Reliability as a Mediating Variable: Study Of Physiotherapy Unit RSO Siaga Raya - Ersa Laila; Endang Ruswanti; Wahyuni Wahyuni (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Background: Brand loyalty reflects patients' tendency to continue using a hospital's services and recommend them to others. However, the decline in physiotherapy patient visits since the COVID-19 pandemic has affected hospital revenue, while brand image and digital marketing via Instagram are still underutilized. Most previous studies have addressed brand loyalty in general, while specific studies on physiotherapy units are still rare. Although many studies show that SMMA and brand image affect loyalty through brand trust, research specifically examining the role of brand reliability as a dimension of trust in healthcare services is still limited.Objective: This study fills this gap by examining the influence of SMMA, brand image, and brand reliability on brand loyalty in the context of physiotherapy services at Siaga Raya Orthopedic Hospital.Methods: This research uses quantitative methods with a purposive sampling technique on 120 respondents. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) method. The study develops the SOR (Stimulus-Organism-Response) theoretical framework.Results: SMMA has a significant effect on brand loyalty both directly and through the mediation of brand reliability. In contrast, brand image requires brand reliability mediation to influence loyalty. Brand reliability proved to be an essential element in building patient loyalty.Implications: Hospitals need to design marketing strategies through social media and brand image that are not only attractive but also reflect service reliability to establish long-term relationships with patients.